Development and Analysis of a New Solar Radiation Atlas for Argentina from Ground-Based Measurements and CERES_SYN1deg data - Carmona, Facundo (2017)
Currently, quantifying global solar radiation at surface in Argentina is crucial for the development of projects related to solar energy, calculation of evapotranspiration and eco-sustainability architecture, among other environmental issues. In recent years, several models have been developed to estimate the solar energy resources by means of various techniques, e.g. satellite imaging, kriging, or Artificial Neural Networks. The use of satellite data allows for a better spatial representation, being of great relevance in areas with lack of terrain measurements. In this paper, we use the CERES_SYN1deg to develop a new Global Solar Radiation Atlas for Argentina. In this study, we developed maps of annual and monthly mean daily global solar radiation using CERES_SYN1deg data between 2000 and 2016. In order to validate the global solar radiation data provided by CERES_SYN1deg, they were compared with ground-based measurements in the time overlap of both instruments, in four monitoring sites of the SAVER-Net project and an additional site in Tandil, which belongs to the Remote Sensing Group of IHLLA. The maps show the spatial and temporal variation of global solar radiation in Argentina. Comparisons with ground-based pyranometers reveal relative differences of around 3% at a monthly scale for all sites, while the biases can be neglected. Therefore, it is possible to conclude that the maps could be very useful for different technical and scientific purposes, and the comparison with ground-based data demonstrates CERES_SYN1deg´s reliability.